A Software Delivery Network-based Approach to Software Ecosystem Evolution Analysis - Pinheiro, Francisco Victor da Silva; Coutinho, Emanuel Ferreira (Anais do Workshop de Visualização, Evolução e Manutenção de Software (VEM); 2023: Anais do XI Workshop de Visualização, Evolução e Manutenção de SoftwareDO - 10.5753/vem.2023.235637, 2023)
Software Ecosystems (SECO) are a set of actors and components that work as a unit, relating to each other based on the common interest of providing solutions or services to the software industry. For a better visualization and understanding of a SECO, recent studies propose the modeling of the formed network. However, there is still no formalized modeling standard for this area. The Software Supply Network (SSN) notation is a series of connected software, hardware, and services organizations that cooperate to meet market demands. In this context, this work aims to present an analysis approach and a study of the SECO evolution based on SSN models. This approach was implemented in a SECO modeling tool.